Kształcenie emisji głosu śpiewanego u dzieci na etapie wczesnej edukacji = The training of voice emission in children at the early education stage - Majzner, Rafał (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The author of the following work attempts to define the concept of the sung voice emission based on available source literature, and indicates the necessity of educating pre-school and early-school children in this field. Furthermore, he also proposes methodical solutions and examples of exercises that can be used during classes in kindergarten and grades 1-3 of primary school.
Keywords: emisja głosu; śpiew; dziecko; edukacja szkolna; edukacja przedszkolna; voice emission; singing; child; pre-school education; early-school education